Promosi Museum Tanah dan Pertanian Sebagai Penguatan Pusat Informasi dan Edukasi Pertanian Tematik - Sutarsyah Sutarsyah; Rima Setiani; Tupan Tupan (Perpustakaan Nasional, 2022)
Soil and Agriculture Museum as a center for information and education in agriculture which is managed by the Center for Library and Agricultural Technology Dissemination. In order to attract visitors, the museum needs to be managed creatively and attractively. This paper aims to provide information to users about the services and activities provided by the Museum of Soil and Agriculture (MTP). Services and activities carried out by libraries and museums to attract users during the COVID-19 pandemic are Virtual Tour MTP, Virtual Tour International Museum Day series, MTP Thematic Exhibition, Sundanese Cultural Creation Dance Competition, Illustration Drawing Competition. In addition to these activities, PUSTAKA also produced five videos which were posted on the Soil and Agriculture Museum Web. The results of activities and promotions carried out by PUSTAKA are then narrated descriptively. The results of the study show that after the promotion of services and activities in 2020 was held, the total visitors to the Soil and Agriculture Museum reached 13,844 people, both directly and via virtually, with students as the most visitors students. It can be concluded that the promotion and service activities carried out can increase the number of visits to the museum.